Modeling Oscillations of Magnetizable Microdrops - G.V. Shagrova; V.I. Drozdova; M.G. Romanenko (Журнал нано- та електронної фізики)
Developed a system of computer simulation of oscillations of magnetizable microdrops in a wide range of changing their parameters: surface tension, viscosity, magnetic permeability, density, and radius. Computational experiments of oscillations of magnetizable drops in an alternating magnetic field and the influence of various forces of nature (inertial, viscous, surface and magnetic) on the nature of the oscillations were carried out. Adequacy of the model, used as the basis for the developed system of computer simulation was shown on the basis of computational and experimental data.